Valdilene Verônica de Albuquerque Lobo: memórias de uma educadora (1978-2008) - Fernandes, Jéssica Luana (2017)
This study aimed to analyze the history and memory of the educational trajectory and political and social engagement of Valdilene Verônica de Albuquerque Lobo in the city of Pau dos Ferros, Northeastern Brazil, from 1978 to 2008. It inquires how did the pedagogical process occur in the political and trade union act in the Association of Teachers of Rio Grande do Norte (APRN) and Workers' Party (PT). It is situated in the field of New Cultural History and has the theoretical and methodological support of studies in the field of memory, biography, oral history and gender, developed by Jacques Le Goff (1990), Maurice Halbwachs (2004), Marie Christine Josso (2010), Verena Alberti (1989), Rachel Soihet (1998), Michelle Perrot (2015), among other studies that articulate the discussions about memory and oral history. Thus, this research was developed through the methodology of interviews with the Thematic Oral History. Some materials that guided the educative practices of Valdilene Lobo in the higher education institution CAMEAM/UERN, as well as her own political engagement material (texts, campaign brochures and some photographs) were used as sources. From the analysis and consideration of the reminiscences of Valdilene Lobo, it was possible to understand the construction of her teacher identity throughout her educational practices situated after the 1964 Brazilian military coup d'état. Thus, her memories unveil the historical context concerning education in Pau dos Ferros. In fact, this biographical research allows us to highlight aspects of the history of education through the memory of an educator, passing through community's political and social events, revealing her educational and political trajectory, and contributing to think about the history of teaching in periods of military dictatorship and re-democratization.